(untitled) (Web of Teachers: Inderscience Research, 2024)
In this article, the author presents an analysis of the ways of developing the creative abilities of children of primary school age by drawing decorative scenery in visual arts classes, as well as their psychological and pedagogical foundations. Also, in the text of the article, the definition given by various scientists to the concept of creative ability in the research, as well as the unique possibilities of developing the visual and creative activity of elementary school students by drawing decorative landscapes, namely, perspective, color, shadow and light in visual arts. An opinion was expressed about the shape, form and lines, the peculiarities of psychological study and several scientific and practical recommendations were developed on this current topic.